POS DILAN (POSYANDU PEDULI LANSIA) DI DESA SUNGAI BEMBAN KEC. KUBU KABUPATEN KUBU RAYA - Eka Riana; Daevi Khairunisa; Galuh Maharani; Farah Oktarini (Politeknik 'Aisyiyah Pontianak, 2024)
Posyandu for the elderly is a place of health services for elderly people (usila) in a certain area. Posyandu for the elderly according to Law no. 13 of 1998 is a forum for services to the elderly in society which focuses on health, psychological and spiritual services, fulfilling nutrition so that the elderly can meet their needs and have adequate social welfare. However, the utilization of posyandu for the elderly is still very far from the target of 90%. Objective: Helping the people of Sungai Bemban Village, especially the elderly of Karya Baru Hamlet, Sungai Bemban Village. Method: This community service was carried out in Sungai Bemban village, Kubu sub-district, Kubu Raya regency on 19-20 September 2021. The target was the elderly. The activities carried out were health checks and elderly exercise. Results: There were 18 elderly people who took part in this pos dilan activity with the majority (72%) experiencing high blood pressure, cholesterol (44%), blood sugar (33%). Conclusion: Dilan Posyandu activities went smoothly, the participants looked enthusiastic about taking part in the posyandu, as well as the cadres who provided support, while most of the elderly did not attend because the examination location was quite far from the elderly's homes.